2012
DOI: 10.1098/rsta.2011.0387
|View full text |Cite
|
Sign up to set email alerts
|

DNA, dichotomic classes and frame synchronization: a quasi-crystal framework

Abstract: In this article, we show how a new mathematical model of the genetic code can be exploited for investigating the almost periodic properties of DNA and mRNA protein-coding sequences. We present the main mathematical features of the model and highlight its connections with both number theory and group theory. The group theoretic framework presents interesting analogies with the theory of crystals. Moreover, we exploit the information provided by dichotomic classes, binary variables naturally derived from the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The analysis of coding sequences of DNA by means of dichotomic classes highlighted the presence of universal strong short-range correlations that can be related to error detection [31,32]. Moreover, the theory of circular codes [52,54,56,58], a class of error detecting codes that have been proposed as strategies for frame detection and maintenance, can also be related to this mathematical framework [64].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of coding sequences of DNA by means of dichotomic classes highlighted the presence of universal strong short-range correlations that can be related to error detection [31,32]. Moreover, the theory of circular codes [52,54,56,58], a class of error detecting codes that have been proposed as strategies for frame detection and maintenance, can also be related to this mathematical framework [64].…”
Section: Resultsmentioning
confidence: 99%
“…These are important to study the problem of retrieving and maintaining of the correct reading frame [45][46][47][48]. The non-power approach allows one to study sequences of DNA and mRNA, including their codon bias, under a new perspective [13][14][15]49] and can lead to new bioinformatics tools and new applications in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…In [14], we have shown that coding sequences are characterized by universal short-range correlations that show up only by looking at dichotomic classes. Moreover, in [15], we have shown that dichotomic classes can be used to design algorithms for frame retrieval.…”
Section: Nnr Xmentioning
confidence: 99%
“…These findings are of particular interest as the information for retrieving the normal reading frame of DNA implies the presence of short-range correlations and almost periodic structures, offering an analogy with the properties of quasicrystals (Giannerini et al, 2012).…”
Section: The Beauty Of Symmetry and The Golden Mean In Biologymentioning
confidence: 99%